Characteristics of UWB propagation through building materials - Jaturatussanai, Pongsatorn; Chamchoy, Monchai; Promwong, Sathaporn (My University, 2005)
UWB system is the one type of several wireless communication that can be used in home networking, which have any probably obstruct by building material. Then the influences of the obstructions are considered. In this paper, the time dispersion and penetration loss are studied. The glass, gypsum, dry wood and partition board are considered the obstruction materials. The channels with these materials are measured in a fully anechoic chamber by using the vector network analyzer. The measurement frequency range is set to be 3-11 GHz, which covered the full band of UWB specified by FCC. The biconical antennas are used for both transmitter and receiver. The time dispersion and penetration loss for each material are evaluated based on the measurement channels. The data of theses results is useful for considering the UWB link budget.
Keywords: Penetration Loss; RMS delay spread; Ultra wideband (UWB)